Tradisi Makan Berhadap Adat Melayu Deli dalam Perspektif Al-Qur'an - Aulia, Shila Dara; Arrahma, Sayla; Safitri, Kayza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Deli Malay tribe is one of the Malay ethnic groups originating from North Sumatra. The majority of the Deli Malay people are located in Deli Serdang, around Medan Madya City. The tradition of eating face-to-face rice began from the past lives of the very Islamic Malay people, where marriages were arranged through matchmaking and family introductions through the tradition of eating face-to-face rice. The purpose of this research is to understand the tradition of eating face-to-face in the Deli Malay tradition from the perspective of the Qur'an. Eating face-to-face is eating together or eating from the same dish. This research uses a descriptive qualitative method to deeply examine eating face-to-face, or what is commonly called face-to-face rice. The research found communication patterns through interviews with one of the researcher's friends. Eating face-to-face rice is one of the highly anticipated customs of the Malay people by both sides of the bride and groom in the marriage process. Eating face-to-face rice is not only for the customary process, but also has many symbolic meanings taken from this customary process. The research results show that the tradition of eating face-to-face is allowed as long as it does not violate religious rules according to Islamic law.